Adaptation of a flowboard for gas exchange studies and a method for capillary calibration - Calbo, Adonai Gimenes (Pesquisa Agropecuaria Brasileira, 2014)
A flowboard or device to mix and control the flow of gases was adapted. The adaptation described allows a mixture of one, two, three or four gases and their flow control through 12 independent outlets. The use of the flowboard manometer for faster capillary check or calibration is suggested. In accordance with this procedure a calibrated capillary having a flow F2, at the pressure gradient P. was connected to the outlet of the capillary under measurement in the flowboard. This connection causes the reading of this particular capillary to be reduced from P to (P - ΔP). The flow under measurement (F1), under the pressure gradient P. was calculated with the expression F1=F2 . ΔP/(P - ΔP).